Integrated DEA and PROMETHEE II method to measure efficiency and complete ranking of Islamic Banks in Malaysia / Nurul Syaerah Robana ... [et al.] - Robana, Nurul Syaerah; Mad Shih, Nur Shakierah; Mohd Firdaus Leong, Natasya; Abd Aziz, Nur Azlina (UiTM Cawangan Negeri Sembilan, 2021)
Data Envelopment Analysis (DEA) approach is a method of assessing efficiency and defining sources and estimating input and output inefficiencies. One of the strengths in DEA is its ability to handle multiple inputs and outputs. It can also identify the best practices among the Decision Making Units (DMUs). The method has been applied extensively in many industries such as insurance, health, education, and banking. However, DEA has some drawbacks and one of them is poor discrimination power where many DMUs are reckoned as efficient units. Standard DEA cannot rank efficient units, hence cannot provide complete ranking of the DMUs. In many situations, fuIly ranking of DMUs is necessary and important to decision makers. Therefore, a method is required to further discriminate among the efficient units. Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE II) is a Multi-Attribute Decision Making method which is based on a common comparison of each different pair with respect to each of the particular criteria. This paper overcomes the ranking problem identified in DEA and achieves fully ranking of the DMUs under study by integrating DEA and PROMETHEE II. The hybrid method was applied to evaluate the efficiency and ranking of 13 Islamic banks in Malaysia from 2017 to 2019.